The Effect of Project-Based Learning in the English for Tourism Course on the Improvement of Students’ Entrepreneurial Communication Skills - Sutanti, Nita; Fauzi, Adin; Fikriya, Silmy (Universitas Islam Balitar, 2025)
This study exmined the effect of Project-Based Learning (PjBL) on students entrepreneurial communication skill in the English for Tourism Course .This study was conducted in English Education Department, Balitar Islamic University Blitar involving the fifth semester students. A one-group pre-test post-test quasy experimental design was applied to measure the effect during the invention. The students were assigned to design, produce and present promotional videos highlighting on tourism destination in Blitar. The project required them to integrate language use with entrepreneurial communication such as persuasion, creativity and confidence in promoting their tourism product. Data were collected through pre-test and post-test speaking skill assessment using a rubric that measured fluency, pronunciation, grammar, vocabulary, content, interaction, presentation, media use, confidence, creativity, and teamwork., The additional data were acquired from classroom observation and questionnaires as project evaluation to attain students engagement and collaborative learning. The Findings showed a significant improvement in students speaking performance, with the mean score increasing from 69.06 in the pre-test to 86.23 in the post-test (t(22) = 14.78, p < 0.001) that indicate PjBL is an effective instructional strategy for enhancing students entrepreneurial communication, as it integrates language proficiency with authentic tourism promotion tasks. The study highlights the potential of PjBL not only to strengthen speaking skills but also to foster creativity, collaboration, and entrepreneurial awareness in English for Tourism education.